2010
DOI: 10.1080/10538720.2010.491747
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Web-Based HIV Prevention for Injection-Drug-Using Black Men Who Have Sex with Both Men and Women: A Feasibility Study

Abstract: This study examined HIV prevention program needs from the perspective of injection-drug-using men who have sex with both men and women (IDU-MSM/W) involved in sex trade. Focus groups were conducted involving an exploratory sample (N = 105) of men who met the following parameters: African American, injection-drugusing behavior, men who have sex with men and women, and men who frequent parks and other areas for sex trade in Baltimore City and surrounding areas, ages 18 to 40 years. Data suggest that an HIV preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(18 reference statements)
1
5
0
1
Order By: Relevance
“…Similar to other programs and studies including social media to improve health (Blas et al, 2007; Chiasson et al, 2010; Kline et al, 2001; Cornelius et al, 2011; Holt et al, 2011; Klein et al, 2010; Levine et al, in press; Rosser et al, 2011; Tsirulink, 2008; Washington & Thomas, 2010; Whittaker et al, 2011; Wilkerson et al, 2011; Wright et al, 2011; Ybarra & Bull, 2007), our findings indicated that multimedia is a feasible method to deliver a health intervention. Furthermore, consistent with previous research (Caetano & Clark, 1998; Stephenson et al, 2008; Warner et al, 2008), our findings provide evidence that online video-based interventions are useful for providing HIV prevention knowledge and knowledge about the importance of testing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to other programs and studies including social media to improve health (Blas et al, 2007; Chiasson et al, 2010; Kline et al, 2001; Cornelius et al, 2011; Holt et al, 2011; Klein et al, 2010; Levine et al, in press; Rosser et al, 2011; Tsirulink, 2008; Washington & Thomas, 2010; Whittaker et al, 2011; Wilkerson et al, 2011; Wright et al, 2011; Ybarra & Bull, 2007), our findings indicated that multimedia is a feasible method to deliver a health intervention. Furthermore, consistent with previous research (Caetano & Clark, 1998; Stephenson et al, 2008; Warner et al, 2008), our findings provide evidence that online video-based interventions are useful for providing HIV prevention knowledge and knowledge about the importance of testing.…”
Section: Discussionsupporting
confidence: 86%
“…This technology is being used already in other sectors, such as social networking and sex seeking websites (e.g., Grindr mobile, adam4adam.com; Chiasson, Hirshfield, & Rietmeijer, 2010; Klein, Lambing, Moskowitz, Washington, & Gilbert, 2010; Washington & Thomas, 2010). Recent health related research indicated that multimedia is a feasible method to deliver health intervention (Blas et al, 2007; Cornelius, Cato, St. Lawrence, Boyer, & Lightfoot, 2011; Levine, Madsen, Barar, Wright, & Bull, in press; Whittaker et al, 2011; Whittaker et al, 2008; Wright, Fortune, Juzang, & Bull, 2011; Ybarra & Bull, 2007).…”
mentioning
confidence: 99%
“…A formative study using focus groups [ 41 ] sought to inform the development of a mobile phone-based HIV intervention; findings suggested the need for a smartphone application or website with a text messaging component. A second feasibility study using focus groups ( N = 105) explored the use of web-based HIV prevention for drug injecting Black MSMW [ 42 ]. Findings suggest the need for dedicated space with HIV prevention programmes for this group of men which should include holistic services including job assistance.…”
Section: Resultsmentioning
confidence: 99%
“…(Mustanski et al 2011 ) is widely available on the Internet, including messages about how to reduce risk (Hightow-Weidman et al 2011 ) and interventions to prevent HIV risk behaviors among MSM (Rhodes et al 2010 ) and blacks who inject drugs (Washington and Thomas 2010 ). Studies show that online delivery of HIV counseling and behavioral interventions for MSM at high risk for HIV are successful, suggesting that the future holds great promise for Internet-delivered interventions for this vulnerable population (Chiasson et al 2009 ;Moskowitz et al 2009 ).…”
Section: Case Descriptionmentioning
confidence: 99%